FACTORS INFLUENCING THE DEVELOPMENT OF NON-AGRICULTURAL BUSINESS ACTIVITIES IN RURAL EASTERN POLAND - Majka, Agnieszka; Zając, Dariusz (Acta Scientiarum Polonorum. Oeconomia, 2019)
The aim of the research was to assess the conditions and identify factors influencing the development of non-agricultural business activities in rural local government areas of Eastern Poland, making use of taxonomic methods and analyses of variance. The empirical content of the article was sourced from the Local Data Bank of Statistics Poland (Bank Danych Lokalnych GUS), including the 2010 Census of Agriculture (Powszechny Spis Rolny 2010), and also data from the Institute of Soil Science and Plant Cultivation (IUNG-PIB) in Puławy. The study findings indicate that rural local government areas of Eastern Poland are strongly differentiated in respect of prevailing conditions for the development of non-agricultural business activities. The most numerous of them was the group consisting of local government areas with moderate conditions while the group of local government areas with better or weaker conditions was less numerous. Moreover, the results of the statistical analysis have shown that significant factors favouring developments of such business activities in rural local government areas of Eastern Poland are essentially the influx of people, municipal investments, as well as European Union financial resources for programs and projects’ implementation.